Numerical Modelling in Enhancing the Water Desalination of Active Solar Still System - Mohamad Shoeb, Mujana (Universiti Teknologi PETRONAS, 2021)
The scarcity of water is amongst many challenges faced by the modern world. It is well established that of the 97% of water on earth, only 0.3% is readily available with minimal treatment. Thus, desalination technologies are adopted as one of the options to solve the said issue. The most suitable, cheap, easy to use and maintain is solar still. In a solar still, natural hydrological cycle is mimicked to produce potable water through evaporation and condensation process. However, most solar stills produce low yield, making it unsustainable over a long period. Fabrication and experimentation required to improve this technology is costly, time and energy consuming, as well as waste of resources. Thus, this research aims to develop a numerical modelling to enhance the water desalination of active solar still using the ANSYS Fluent 19.2, a Computational Fluid Dynamic (CFD) analysis software.